AN ANALYSIS OF THE RETENTION OF DISTANCE LEARNING VIA DLTV USING COST-EFFECTIVENESS ANALYSIS - inrongpon, phitchakorn; Kiettikunwong, Narong (Journal of Humanities and Social Sciences Mahamakut Buddhist University Isan Campus, 2025)
This research evaluates the cost-effectiveness of the Satellite-Based Distance Learning Media (DLTV) policy in early childhood development centers in Phu Wiang District, Khon Kaen Province, with a total of 28 centers, following the COVID-19 situation. The study examines the appropriateness and efficient use of resources. The research applied a qualitative methodology through data analysis, which was carried out by reviewing related documents from academic databases, online sources, and libraries. Since this study analyzes data from documents and secondary sources, there is no sample group in the form of quantitative data collection. The findings revealed that DLTV has low maintenance costs, content development costs, and project management costs when compared to other teaching media. DLTV helps improve access to education, reduces disparities, and expands opportunities for disadvantaged groups. However, a limitation of DLTV is the lack of interaction and content customization for specific learner groups. In the long term, DLTV has the potential to be used in areas with resource and budget constraints, but content development and additional media should be incorporated to enhance learning effectiveness. In conclusion, DLTV is a low-cost medium that provides broad educational benefits and is suitable for resource-scarce areas, but improvements are needed in terms of interaction and content flexibility.